Exploring Written and Unwritten Curricular Practices in Nepal's Community Schools: Impact on Student Outcomes - Bisna Acharya; Surya Sigdel (ABM: International Journal of Administration, Business and Management, 2024)
To effectively achieve the objective of this research, a thorough analysis will be conducted on the implementation of the curriculum in school education. This analysis will encompass both the visible and concealed components, with the aim of identifying any shortcomings in the curriculum. A study was conducted in the community schools of Kathmandu to examine the factors that contribute to the difference between the expected learning outcomes of school education and the actual results outlined in the curriculum. Throughout the investigation, students and teachers from five community schools situated on the outskirts of Kathmandu's suburbs enthusiastically took part. The authors utilized a range of methods to collect data, such as conducting in-depth interviews, leading group discussions, and making direct observations. Based on the findings of the study, it has been concluded that educational activities that prioritize the development of meaningful connections offer more benefits compared to those that hinder the acquisition of practical knowledge and skills. The curriculum provides the necessary resources to support instructional activities that are guided by instructors and actively engage learners. Students can develop essential academic and cross-curricular skills with the help of this approach. In order to promote the development of students with diverse abilities and knowledge, it is crucial for the curriculum to acknowledge the negative impact of insufficient instruction and an excessive focus on high-stakes assessments. Due to this, there has been a strong focus on instructional and learning strategies that prioritize examinations.